Liberalism and its discontents - Francis Fukuyama (New York : Farrar Straus and Giroux, 2022)
"A short book about the challenges to liberalism from the right and the left by the bestselling author of The Origins of Political Order"
Includes bibliographical references and index.
Keywords: Liberalism